Observations of the Structure and Dynamics of the Inner M87 Jet - R. Craig Walker; Philip E. Hardee; Fred Davies; Chun Ly; William Junor; Florent Mertens; Andrei Lobanov (Galaxies, 2016)
M87 is the best source in which to study a jet at high resolution in gravitational units because it has a very high mass black hole and is nearby. The angular size of the black hole is second only to Sgr A*, which does not have a strong jet. The jet structure is edge brightened with a wide opening angle base and a weak counterjet. We have roughly annual observations for 17 years plus intensive monitoring at three week intervals for a year and five day intervals for 2.5 months made with the Very Long Baseline Array (VLBA) at 43 GHz. The inner jet shows very complex dynamics, with apparent motions both along and across the jet. Speeds from zero to over 2c are seen, with acceleration observed over the first 3 milli-arcseconds. The counterjet decreases in brightness much more rapidly than the main jet, as is expected from relativistic beaming in an accelerating jet oriented near the line-of-sight. Details of the structure and dynamics are discussed. The roughly annual observations show side-to-side motion of the whole jet with a characteristic time scale of about 9 years.